(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2026)
This study aimed to analyze the impact of digital transformation in its various dimensions (digital strategy, technologies, digital customer loyalty, culture and organization, operations and services) on the performance efficiency of Jordanian Islamic banks, represented by dimensions (banking marketing efficiency, risk management efficiency, financial engineering efficiency), while testing the role of Sharia quality as a moderating variable in this relationship. The study was applied to a sample of 354 employees working in three Islamic banks: Jordan Islamic Bank, Arab Islamic International Bank, and Safwa Bank. The study used a descriptive analytical approach, and data was collected through a questionnaire and then analyzed using SPSS and Smart PLS software. The results showed a statistically significant impact of digital transformation in all its dimensions on the performance efficiency of Islamic banks. The interactive relationship also revealed the impact of Sharia quality as a moderating variable in some dimensions, using Bootstrap technology and structural equation modeling. The study recommended establishing a joint unit between financial innovation and Sharia compliance to develop flexible digital products that serve underserved groups, especially young people and entrepreneurs, while ensuring their Sharia compliance